Overproduction, purification, and characterization of heat stable aldolase from Methanococcus jannaschii, a hyperthermophic archaea - Choi, IG; Cho, CS; Cho, YJ; Yu, YG (SPRINGER-VERLAG SINGAPORE PTE LTD, 1998)
An aldolase gene has been cloned from Methanococcus jannaschii. The coding region of the gene has been expressed in E. coli using a pET system to a level of 30% of total cellular proteins. The protein was performed to more than 95% homogeneity by heat treatment and ion exchange chromatography. The protein performed an aldol condensation reaction with glyceraldehyde as substrate and dihydroxyacetone phosphate as a carboxyl donor. The protein was determined to be a type II aldolase which requires the Zn2+ ion as a metal cofactor. This enzyme has a broad range of optimum pH (7-9) and temperature (58-80 degrees C). It shows strong stability against heat, chemical denaturants, as well as a high percentage of organic solvents. The half-life of this enzyme at 85 degrees C is more than 24 h and it maintains more than 90% of aldolase activity in the presence of 6 M urea, 50% acetonitrile, or 15% isopropyl alcohol.
Keywords: ESCHERICHIA-COLI; SEQUENCE